2022
DOI: 10.1186/s12284-022-00588-y
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Acts Upstream of Auxin and Nitric Oxide (NO) in Cell Wall Phosphorus Remobilization in Phosphorus Deficient Rice

Abstract: Salicylic acid (SA) is thought to be involved in phosphorus (P) stress response in plants, but the underlying molecular mechanisms are poorly understood. Here, we showed that P deficiency significantly increased the endogenous SA content by inducing the SA synthesis pathway, especially for up-regulating the expression of PAL3. Furthermore, rice SA synthetic mutants pal3 exhibited the decreased root and shoot soluble P content, indicating that SA is involved in P homeostasis in plants. Subsequently, application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…They are synthesized in the Golgi apparatus and subsequently transported to the cell wall, where they regulate cell wall properties such as extensibility and thickness [34]. Pectin polysaccharide is the major binding and accumulation site for HMs in the cell wall due to the presence of homogalacturonan in addition to rhamnogalacturonan-I and rhamnogalacturonan-II [35]. Pectin demethylation is carried out by pectin methylesterase (PME), which is an important process in cell walls to adsorb HMs and enhance their capacity for binding HMs [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are synthesized in the Golgi apparatus and subsequently transported to the cell wall, where they regulate cell wall properties such as extensibility and thickness [34]. Pectin polysaccharide is the major binding and accumulation site for HMs in the cell wall due to the presence of homogalacturonan in addition to rhamnogalacturonan-I and rhamnogalacturonan-II [35]. Pectin demethylation is carried out by pectin methylesterase (PME), which is an important process in cell walls to adsorb HMs and enhance their capacity for binding HMs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose, hemicellulose, lignin, and pectin pathways were activated under Cr stress with or without Pro application (Figure 1). Based on the data of microarray analysis, a total of 203 genes associated with the four pathways of plant cell wall components, i.e., cellulose (60), hemicellulose (57), lignin (35), and pectin (51), were detected. All the data related to these genes, i.e., enzyme name, gene name, chromosome locus, and Cr-concentration-dependent up/downregulation in roots and shoots, are provided in Supplementary Data S1.…”
Section: Identification Of Genes Involved In Cell Wall Componentsmentioning
confidence: 99%
“…Elevated PME activity can facilitate the remobilization of P deposited in the cell wall (Zhu et al, 2016). Wu et al (2022) found that OsPME14 overexpression increased PME activity, released more P from the root cell wall, and improved plant resistance to P deficiency. Zhu et al (2018) reported that in O. sativa, NO − 3 deficiency caused higher levels of nitric oxide to accumulate in the roots and increased the activity of nitrate reductase.…”
Section: Genes and Metabolites Associated With Cell Wall Reprogrammin...mentioning
confidence: 99%
“…Liu et al (2019) found that HvEXPA1 participates in root cell elongation and influences Al content by regulating root cell wall loosening when exposed to Al stress. Wu et al (2022) screened 40 differentially expressed expansin genes in roots of oilseed rape (Brassica napus) in response to boron deficiency. Similar results were also reported by Nezamivand-Chegini et al (2022).…”
Section: Expansin Involved In Apple Dwarfing Rootstock Morphogenesis ...mentioning
confidence: 99%
“…On the exogenous application of PME combined with calcium chloride, the fruit softening of raspberry was delayed due to an extended maintenance of cell wall integrity [7]. Moreover, by increasing the PME activity, the phosphorus fixed in the cell wall was remobilized [8]. During lettuce seed germination, the PME activity was lower in the endosperm cap, but higher in the radicle [9].…”
Section: Introductionmentioning
confidence: 99%